2000
DOI: 10.1162/003465300558560
|View full text |Cite
|
Sign up to set email alerts
|

Why do Banks Disappear? The Determinants of U.S. Bank Failures and Acquisitions

Abstract: This paper examines the determinants of individual bank failures and acquisitions in the UnitedStates during 1984-1993. We use bank-specific information suggested by examiner CAMELrating categories to estimate competing-risks hazard models with time-varying covariates. We focus especially on the role of management quality, as reflected in alternative measures of xefficiency and find the inefficiency increases the risk of failure, while reducing the probability of a bank's being acquired. Finally, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
296
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 543 publications
(322 citation statements)
references
References 31 publications
(13 reference statements)
22
296
2
2
Order By: Relevance
“…As a consequence, this procedure can lead to an increase in bank costs. Consistent with the 'bad luck hypothesis', Wheelock and Wilson (2000) find that inefficient banks are closer to failure. Similarly, investment banks' performance (measured by cost efficiency) is negatively associated with insolvency risk as defined by the Z-Score (Radic et al, 2012).…”
Section: Hypotheses Developmentsupporting
confidence: 57%
“…As a consequence, this procedure can lead to an increase in bank costs. Consistent with the 'bad luck hypothesis', Wheelock and Wilson (2000) find that inefficient banks are closer to failure. Similarly, investment banks' performance (measured by cost efficiency) is negatively associated with insolvency risk as defined by the Z-Score (Radic et al, 2012).…”
Section: Hypotheses Developmentsupporting
confidence: 57%
“…Beck (2008) argues that while stability is inherently important the primary concern of policy makers should be on a regulatory framework to support a competitive and efficient financial market that will allocate savings to their best possible use and support real markets. Furthermore, the literature suggests a direct link between inefficiency and the risk of bank failure (Wheelock and Wilson, 2000), and between inefficiency and problem loans, the latter being associated with adverse selection problems (Berger and DeYoung, 1997). Seen in the above context, our study highlights the importance of designing an appropriate bank regulatory and supervisory framework that helps maintain the efficiency (and hopefully stability) of banks.…”
Section: Discussionmentioning
confidence: 72%
“…Bank crises are more likely in countries with low GDP growth, high real interest rates, high inflation rates, and explicit deposit insurance system. Countries that are more susceptible to balance of payment crises also have a higher probability of experiencing banking crises [17], [18] found that banks with lower capitalisation, higher ratios of loans to assets, poor quality loan portfolios and lower earnings have higher risk of failure US collapsed banks increased significantly in 2009 with a total of 72 as compared to only 25 collapsed banks in 2008. In 2007, there were only three.…”
Section: Financial Distressed Banksmentioning
confidence: 99%